Biological control as a key tool for the management of invasive species in Latin America and the Caribbean - Colmenárez, Yelitza [UNESP]; Vásquez, Carlos; Fidelis, Elisangela Gomes; Corniani, Natalia [UNESP] (Springer Nature, 2020)
The attack of pests and diseases represents one of the main limitations for agricultural production in the Neotropical region. The intensification of trade between Latin American countries, the Caribbean, and other regions, among other factors, has resulted in the introduction of a large number of invasive pests in the Neotropical region, affecting crop production and causing large significant losses. Despite efforts to prevent their entry to Latin America and the Caribbean, through the establishment of quarantine systems in the different countries and the implementation of tactics to reinforce phytosanitary surveillance, each year new pests are reported to be introduced in areas where they were not present. This when added to the effects of climate change, represents a challenge for plant protection since it favours the displacement of pests to new areas due to the increase of temperature and changes in the climatic conditions, facilitating the establishment of some introduced species. This chapter presents the use of biological control agents through the implementation of programmes adapted to local conditions as a key strategy for the sustainable management of pests currently present in and potential pests to the region. Initiatives are also presented to strengthen the quarantine system and phytosanitary surveillance in a joint effort with institutions and government agencies of the countries where CABI implements the Plantwise and Action on Invasives programmes, and sustainable production projects with the objective of reinforcing food security in Latin American and the Caribbean countries.
Keywords: Biological control; Climate change; Invasive species; Neotropic; Plant protection